Associations of antimicrobial use with antimicrobial resistance in Campylobacter coli from grow-finish pigs in Japan - Ozawa, M.; Makita, K.; Tamura, Y.; Asai, T. (Elsevier, 2012)
To determine associations between antimicrobial use and antimicrobialresistance in Campylobactercoli, 155 isolates were obtained from the feces of apparently healthy grow-finishpigs in Japan. In addition, data on the use of antibiotics collected through the national antimicrobialresistance monitoring system in Japan were used for the analysis. Logistic regression was used to identify risk factors to antimicrobialresistance in C. coli in pigs for the following antimicrobials: ampicillin, dihydrostreptomycin, erythromycin, oxytetracycline, chloramphenicol, and enrofloxacin. The data suggested the involvement of several different mechanisms of resistance selection. The statistical relationships were suggestive of co-selection; use of macrolides was associated with enrofloxacin resistance (OR = 2.94; CI95%: 0.997, 8.68) and use of tetracyclines was associated with chloramphenicol resistance (OR = 2.37; CI95%: 1.08, 5.19). The statistical relationships were suggestive of cross-resistance: use of macrolides was associated with erythromycin resistance (OR = 9.36; CI95%: 2.96, 29.62) and the use of phenicols was associated with chloramphenicol resistance (OR = 11.83; CI95%: 1.41, 99.44). These data showed that the use of antimicrobials in pigs selects for resistance in C. coli within and between classes of antimicrobials.